SERVICE TO STUDENTS WITH CULTURAL DIVERSITY, SOCIO ECONOMIC, INTELLIGENCE AND LEARNING STYLES - Hermino, Dr. Agustinus (IJRDO - Journal of Applied Management Science, 2016)
Education is the key word in any effort to improve the quality of human life within which it has a role and a purpose for ’humanizing’, and process of maturation quality of life. Through the process is expected to be able to understand what is the meaning the essence of life, and for what and how to carry out the task of living and life correctly. That’s why the focus of education is directed to the formation of a superior personality with emphasis on the quality of the maturation process of logic, heart, character, and faith. The highlight was reaching the point of perfection education quality of life. The task of education also to motivate each student to identify potential as early as possible, and schools provide services in accordance with its potential and directs the preparation for the challenges ahead. Education leads to the formation of character, performance concrete and measurable that develops in three domains capabilitie: cognitive, psychomotor, and affective. Multicultural means diversity of culture. The roots of multiculturalism is the culture, that viewed from its function as a guide for human life. In the context of nation building, this multicultural term has formed an ideology in a wide range of experiences that shape popular perceptions of age, gender, religion, socioeconomic status, type of cultural identity, language, race, and disability. Organizational culture at the school level requires the ability to mobilize the developments and changes that do creative activities, identify strategies, methods, means, or new concepts in teaching so that meaningful learning and delivery of quality education